2007
DOI: 10.1016/j.febslet.2007.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Cell stress induced HSP are targets of regulatory T cells: A role for HSP inducing compounds as anti‐inflammatory immuno‐modulators?

Abstract: T cell responses to heat shock proteins (HSP) have disease suppressive activities through production of anti-inflammatory cytokines in patients and in models of inflammatory diseases. There is evidence that the anti-inflammatory activity of HSP-specific T cells depends on their recognition of endogenous HSP epitopes as expressed by stressed cells at sites of inflammation. Previously, we have demonstrated that such T cells can be induced by conserved sequences of microbial HSP. Now we propose that drug induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 58 publications
1
61
0
Order By: Relevance
“…Self-Hsp cross-reactive T cells are thought to be present at the site of inflammation and are able to enhance the production of regulatory cytokines as IL-10 and TGF-β (Hauet-Broere et al 2006;Wieten et al 2007). Another interesting finding is that, in human atopic lesional skin, expression of Hsp70 and Hsp60 is more intensive than in normal healthy skin (Ghoreishi 2000).…”
Section: Discussionmentioning
confidence: 88%
“…Self-Hsp cross-reactive T cells are thought to be present at the site of inflammation and are able to enhance the production of regulatory cytokines as IL-10 and TGF-β (Hauet-Broere et al 2006;Wieten et al 2007). Another interesting finding is that, in human atopic lesional skin, expression of Hsp70 and Hsp60 is more intensive than in normal healthy skin (Ghoreishi 2000).…”
Section: Discussionmentioning
confidence: 88%
“…Hsp70 is a protein with powerful immunological properties: it has been associated with the innate immune response (Triantafilou et al 2008), and a strong binding to B cells, which are responsible for antibody production, has been shown (Asea 2005). Although there are several studies that link immunity to Hsp70 in the promotion of chronic inflammatory conditions such as multiple sclerosis, diabetes, and cardiovascular disease, many other studies show that such immune response attenuates inflammatory disease (Wieten et al 2007). Specifically, it has been shown that patients with stable and unstable angina (Herz et al 2006) and with acute coronary syndrome (Zhang et al 2010) have lower levels of anti-Hsp70 antibodies than the healthy population and that microvascular and macrovascular complications in patients with type 1 diabetes positively correlate with lower levels of anti-Hsp70 and anti-Hsp60 antibodies (Gruden et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…36,37,42,43 HSP90 has been implicated in studies investigating similar autoimmune diseases and it has been reported that T cells respond to extracellular HSP90 by increasing their anti-inflammatory cytokines. 44 Other recent work has shown that T-cell activation by the T-cell receptor is dependent on functioning HSP90. 45 Despite findings suggesting a role for HSP90 in SLE, or the antiinflammatory effects of HSP90 inhibition, little has been published exploring the effect of HSP90 inhibition in SLE.…”
Section: Introductionmentioning
confidence: 97%